A battery integrated three‐port bidirectional charger/discharger for light electric vehicles with G2V and V2G power flow capability. (16th May 2021) - Kumar, Deepak; Saxena, Anmol Ratna
Summary: In this paper, a non‐isolated battery integrated three‐port bidirectional dc‐dc converter (BIBTPC) is proposed and analyzed for interfacing light electric vehicles (LEVs) with solar photovoltaic (SPV)‐fed low voltage dc distribution system (LVDDS). Depending upon the power generation, the converter can be controlled to operate in grid‐to‐vehicle (G2V) or vehicle‐to‐grid (V2G) arrangement. BIBTPC can implement maximum power point tracking (MPPT), simultaneously regulating the dc bus voltage of LVDDS. It also has an inherent feature of pulse charging and pulse discharging of the battery which improves its charging/discharging rate. The converter operation in all the possible modes is elucidated, and steady‐state analysis is performed to establish the key performance features. The guidelines for the inductor and capacitor design of the converter are also presented. The control strategy to ensure MPPT simultaneously managing the power flow among SPV, LVDDS, and LEV battery is developed and implemented. The theoretical predictions are validated experimentally on the laboratory prototype of the converter. These results are found to be in close agreement with each other. Abstract : A non‐isolated battery integrated three‐port bidirectional dc‐dc converter (BIBTPC) is proposed and analysed for interfacing light electric vehicles (LEVs) with solar photovoltaic (SPV) fed low voltage dc distribution system (LVDDS). Depending upon the power generation, the converter can be controlled to operate in grid‐to‐vehicle (G2V) or vehicle‐to‐grid (V2G) arrangement. BIBTPC can implement maximum power point tracking (MPPT) simultaneously regulating the dc bus voltage of LVDDS.